2020
DOI: 10.3762/bjoc.16.135
|View full text |Cite
|
Sign up to set email alerts
|

Fluorohydration of alkynes via I(I)/I(III) catalysis

Abstract: Substrate specificity is ubiquitous in biological catalysis, but less pervasive in the realm of small-molecule catalysis. Herein, we disclose an intriguing example of substrate specificity that was observed whilst exploring catalysis-based routes to generate α-fluoroketones from terminal and internal alkynes under the auspices of I(I)/I(III) catalysis. Utilising p-TolI as an inexpensive organocatalyst with Selectfluor® and amine/HF mixtures, the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…However, slower reaction rates have been observed with electron-rich substrates, probably due to competitive side reactions such as formation of diaryl iodanes. , The main parameter affecting the overall reaction rate was found to be the substitution of the iodoarene (Figure b). The obtained negative ρ value (−1.95) strongly indicates a buildup of positive charge on the iodine atom of the iodoarene (oxidation) as the rate-limiting step.…”
Section: Mechanistic Investigationssupporting
confidence: 91%
See 1 more Smart Citation
“…However, slower reaction rates have been observed with electron-rich substrates, probably due to competitive side reactions such as formation of diaryl iodanes. , The main parameter affecting the overall reaction rate was found to be the substitution of the iodoarene (Figure b). The obtained negative ρ value (−1.95) strongly indicates a buildup of positive charge on the iodine atom of the iodoarene (oxidation) as the rate-limiting step.…”
Section: Mechanistic Investigationssupporting
confidence: 91%
“…18,28 The main parameter affecting the overall reaction rate was found to be the substitution of the iodoarene (Figure 1b). The obtained negative ρ value (−1.95) 29 strongly indicates a buildup of positive charge on the iodine atom of the iodoarene (oxidation) as the rate-limiting step.…”
Section: ■ Mechanistic Investigationsmentioning
confidence: 99%
“…The dominant formation of the cis isomer suggests that the ester functionality may play a role in coordinating the iodine­(III) species to the same face of the alkene. This coordinating role of the ester is well-established in the I­(I)/I­(III)-catalyzed fluorohydration of alkynes (the fluoro-Kucherov reaction) and supported by the observation that CO 2 Me → SO 2 Ph exchange erodes stereoselectivity ( 3q ; Scheme ). Fluorination to generate the cyclobutane II would enable a stereospecific ring contraction to liberate the catalyst and generate a cis -configured cyclopropyl carbinyl cation.…”
mentioning
confidence: 72%
“…Very recently, α‐fluoroketones were readily synthesized from terminal and internal alkynes via I(I)/I(III) catalysis utilizing p ‐TolI as an organocatalyst with selectfluor, water, and amine ⋅ HF mixtures . Selectfluor‐mediated oxidation of p ‐TolI in the presence of an amine ⋅ HF source in situ generated p ‐TolIF 2 , which productively engaged with pentynyl benzoates to form the desired α‐fluoroketones.…”
Section: Fluorination Mediated By Hypervalent Iodine Reagentsmentioning
confidence: 99%
“…Preliminary mechanistic studies, including Hammett analyses, identified the importance of the pentynyl linker and the benzoyl ester in the substrates, which were the key determinants for reaction efficiency, suggesting a highly preorganised structure. Although the origin of this specificity requires clarification, this fluorohydration constituted a rare case of substrate specificity in small‐molecule catalysis …”
Section: Fluorination Mediated By Hypervalent Iodine Reagentsmentioning
confidence: 99%